A first course in design and analysis of experiments - Oehlert, Gary W. (W.H. Freeman, 2000)
Oehlert's text is suitable for either a service course for non-statistics graduate students or for statistics majors. Unlike most texts for the one-term grad/upper level course on experimental design, Oehlert's new book offers a superb balance of both analysis and design, presenting three practical themes to students: when to use various designs, how to analyze the results, how to recognize various design options